Climate change and indigenous community: Review on livelihoods challenges and dependency on non-timber forest products (NTFP) / Mohamad Syahmi Mat Daud ... [et al.] - Mat Daud, Mohamad Syahmi; Yahaya, Fatan Hamamah; Tuan Lonik, Ku 'Azam; Mustaffa, Mohd Shahrol Hapizam (Universiti Teknologi MARA Cawangan Pahang, 2020)
The Malaysian indigenous communities has lived in a remote section of the state for generations. This communities have traditionally managed and relied on forests for hunting, fishing and natural resources. In this study, we attempts to discuss the impact of climate change on indigenous communities livelihoods and their dependency on forest resources, specifically non-timber forest products (NTFPs). This paper adopts a review approach using the indigenous peoples and non-timber forest products as a case study. This review shows that climate change is affecting indigenous people livelihoods negatively since the NTFPs become more limited and vulnerable. We recommend that climate change adaptation initiatives for remote communities of Malaysia should focus in improving the socio-economic status and sustainable development of the indigenous community. Furthermore, effective strategies for planning and implementing are crucial to identify the constraints faced by indigenous people.